PENGARUH PENERAPAN ASESMEN DIAGNOSTIK NON-KOGNITIF TERHADAP GAYA BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI FASE (E) DI SMA NEGERI 1 SALIMPAUNG - Hanifah, Nurul; Faishal Yasin; Yanti Sriwahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Diagnostic assessment is an initial evaluation conducted before or during the learning process to determine students' abilities, characteristics, strengths, and weaknesses. Students' low understanding of the material and a lack of attention to diverse learning styles make the learning process less effective. This research aims to examine the influence of non-cognitive diagnostic assessment on the learning styles of sociology students in Class X at SMAN 1 Salimpaung.The theory used in this research is constructivism according to Jean Piaget. The method employed is quantitative with a descriptive approach. The population for this study comprises Class X Phase E students, and the sample is Class X E2, with the researchers using Purposive Sampling to select the sample. The research instruments used include questionnaires, observation, and document study. Data for this study were collected through questionnaires distributed to 32 students and observations during the learning process. The questionnaire consisted of 32 statements regarding visual, auditory, and kinesthetic learning styles. Data analysis in this study involved validity testing, reliability testing, normality testing, linearity testing, and hypothesis testing.The results of this study indicate that there is a diversity of student learning styles in Class X E2 SMAN 1 Salimpaung, with the visual learning style being more dominant. The application of non-cognitive diagnostic assessment significantly influenced students' understanding of their learning style characteristics. Consequently, teachers can more easily design appropriate learning strategies and improve student learning outcomes. It is recommended that teachers regularly conduct this assessment to make the teaching and learning process more effective and enjoyable for students.